Smartphone Use While Driving: An Investigation of Young Novice Driver (YND) Behaviour. (February 2021) - Jannusch, Tim; Shannon, Darren; Völler, Michaele; Murphy, Finbarr; Mullins, Martin
Highlights: Risky driving behaviours are compared against smartphone-use behaviours while driving. A representative sample of 700 German Young Novice Drivers (YNDs) was used. An updated German version of the Behaviour of Young Novice Drivers Scale (BYNDS) was applied. A group of high-risk 'problem' young drivers was identified. Policy-relevant suggestions are provided on the issue of smartphone use while driving. Abstract: Road traffic collisions are the leading cause of death for those between the ages of 15–29, according to the World Health Organisation. This study investigates one of the primary reasons for the high fatality rate amongst Young Novice Drivers (YNDs) – their use of smartphones while driving. We gathered responses from a representative sample of YNDs on their behaviour while driving using an updated version of the 'Behaviour of Young Novice Drivers Scale'. Survey responses totalled 700 YNDs situated throughout Germany. From these responses, we examined the prevalence of certain driving behaviours that are described as 'distracting' and compared these driving behaviours to the respondents' use of specific smartphone features. The responses report that music-related activities (e.g. changing music on a smartphone) are most common amongst YNDs. Speaking on the phone is seldom-reported, although more males than females indicated engagement in this behaviour. We further carried out a correlation analysis and correspondence analysis. On that basis we found that those who report speaking on a smartphone are significantly more likely to engage in driving behaviours with potentially fatal consequences, such as speeding and driving while impaired by prohibited substances (drugs, alcohol). We propose that the results could be used by policymakers for public information implications and to tailor financial penalties for those engaging in smartphone behaviours that are linked to harmful driving behaviours. In addition, our findings can also be used in a Usage-based Insurance (UBI) context to financially incentivise safer driving.